Where Science Fails, Outdated Religion Provides Clues - G., Venkatesh (Problemy Ekorozwoju, 2017)
Solutions to challenges, and answers to questions are often to be found in what we normally overlook, downplay and reject and deny. The Ask and it will be given to you; seek and you will find; knock and the door will be opened to you of the Holy Bible refers to seeking there where one normally would not expect to find anything. The caste-system which prevailed in ancient Hindu society (and still does, though not as prominently as before) does have some hidden lessons for the modern Hindu (in India or in the wider Indian diaspora), which could be very valuable for sustainable development.